Analisis Penerapan Strategi Promosi Dalam Meningkatkan Penjualan Pada Usaha Cafe di Kecamatan Sungailiat (Studi Kasus) - Fachrul Haitami; Siti Napisah (JEM Jurnal Ekonomi dan Manajemen, 2022)
This study aims to analyze the Implementation of Promotional Strategies in Increasing Sales. Based on the research conducted, the results and conclusions are as follows: first, the internet cafe business in Sungailiat sub-district has used several promotional strategies in increasing sales, but in its application, it is still not optimal and only uses several strategies. , such as advertising (advertising) where only 50% of the advertising strategy is applied, 50% of internet cafe businesses that implement this advertising strategy for example use social media (Instagram, Facebook, and WhatsApp) and some use brochures, word of mouth and so on. Second, several internet cafe businesses in Sungailiat sub-district that implement sales promotions only apply 70% of this sales promotion strategy. As for the ways that are done by giving gifts (souvenirs), reducing prices, giving discounts, holding giveaways, and giving vouchers, there is also giving cashback to consumers and taking advantage of existing events. And third, the implementation of the face-to-face selling strategy (personal selling) which is applied to the internet cafe business in Sungailiat District, the personal selling strategy is carried out 100% by internet cafe business actors in Sungailiat District which includes direct interaction (face-to-face), and to encourage sales during the pandemic. During this covid-19 pandemic, the internet cafe business uses several methods, including sales via WhatsApp (delivery) and take away.